Using the Finnish Doppler lidar network to study elevated aerosol depolariation ratio at 1565 nm - Lobo, Hannah (Helsingin yliopisto, 2021)
The lidar depolarisation ratio is used for aerosol categorisation as it is indicative of aerosol shape. Commonly, depolarisation ratio is measured in short term studies at short wavelengths such as 355 nm and 532 nm. The depolarisation ratio has a spectral dependency and so exploring values at longer wavelengths could be valuable for future studies. Here, aerosol depolarisation ratio at 1565 nm is measured across Finland’s ground based remote sensing network over a four year period. The Halo Photonics StreamLine Doppler lidars instruments were found to be stable over long time periods and cloud based calibration was used to correct for the bleed though. The depolarisation ratio of elevated aerosol layers was compared to boundary layer aerosol. A higher average depolarisation ratio was found for elevated aerosol with the exception of boreal forest sites in the summer months where values were similar. Elevated aerosols over Finland were found to originate mostly from the Arctic, Europe, Russia and North America using aerosol transport models. Four case studies were looked at in more detail: Saharan dust with a depolarisation ratio of 0.249 ± 0.018, pollen with a depolarisation ratio of 0.207 ± 0.013, anthropogenic pollution with a depolarisation ratio of 0.067 ± 0.009, and a mixed layer with a depolarisation ratio of 0.152 ± 0.019 thought to be pollen and smoke. Based on this study, Halo Doppler Lidar can be used to measure elevated aerosol at 1565 nm in the long term. Future studies could use 1565 nm depolarisation ratio alongside commonly used shorter wavelengths to aid aerosol categorisation.